Educação e trabalho: perspectivas de estudantes do ensino médio de uma escola pública do município de Upanema – RN - Bezerra, Gislaine Mendonça (Universidade Federal Rural do Semi-Árido, 2021)
When young people enter High School, they go through questions about what will happen after completing the Basic Education cycle, since at this time they will have to choose which path to take, whether they will enter higher education and/or the labor market. even at this stage, they must have family and school support so that they can contribute to their life project. Thus, this work has as its main theme "Education and Work: perspectives of high school students from a public school in the city of Upanema - RN", containing as a study problem "What perspectives of young people, graduates of high school, from a public school in the city of Upanema-RN on education and work?”. In this way, the general objective is “Analyzing the perspective of young people graduating from high school at a public school in the city of Upanema-RN on education and work”. The specific objectives include: (a) Evidencing the perspective on education and work of young people, graduates of high school in a public school in the Municipality of Upanema – RN; (b) Identify the participation of the school and the family in the social development of young people who have completed high school at a public school in the Municipality of Upanema – RN; (c) Thinking about how the public school prepares young people, who are graduating from high school, to enter the university and/or the job market. For this purpose, a qualitative approach was chosen, which allowed the production of data through the elaboration of a questionnaire with 11 (eleven) open and closed questions. The research was carried out at the José Calazans Freire State School which is located in the Municipality of Upanema – RN, given this fact, it was possible to apply the questionnaire in the class of the 3rd year “A”, of the morning shift, which contains 35 students. The survey was developed using the google form. In conclusion, it is highlighted that most young people intend to enter Higher Education after completing High School. This demonstrates that they are looking to qualify and qualify for the job market. Another aspect identified in the study is consistent with the fact that most young people participating in the research have family support to continue their studies and develop socially. However, the distancing of the family from the school environment is emphasized, thus affecting the progress of subjects in the learning process, as both instances are essential in the formation of youth identity, as well as in the construction of the youth's life project.
Keywords: Perspectiva juvenil; Educação; Desenvolvimento social; Trabalho; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL